Pertumbuhan Abalon Tropis (Haliotis squamata) pada Pemberian Pakan Dua Makroalga yang Berbeda di Wadah Pemeliharaan - Idham S. Pratama; Yanuariska Putra; Dien A. Anggorowati; Evi A. Siahaan; La Ali (Fakultas Ilmu Kelautan dan Perikanan (FIKP), Universitas Hasanuddin, 2022)
Macroalgae Gracilaria sp. and Ulva sp. are commonly found, cultivated, and utilized to feed abalone in captivity. This study was aimed to evaluate the effect of two different macroalgae diet (Gracilaria sp. and Ulva sp.) on tropical abalone (Haliotis squamata). Two treatments of macroalgae diet (Gracilaria - Gra and Ulva - Ulv) with six replications were performed at Research Center for Marine and Land Bioindustry, North Lombok. In this study, 300 tropical abalone (49.40 ± 0.21 mm) were kept indoor in 60-l rearing tank at 25 abalone per tank of stocking density for 90 days between September to December. Macroalgae Gracilaria sp. outperformed Ulva sp. on specific growth rate body weight (SGRBW) (0.18 ± 0.15), food conversion ratio (FCR) (7.14 ± 5.72) and survival rate (SR) (75.20 ± 15.34 %) of tropical abalone.